Labrador, aerial view of mountains - Forbes, Alexander, 1882-1965 (1931)
(Series 29) Inland flight from the drainage basin of the Eclipse River to the Central Range, gradually crossing it, and then proceeding to the west of it until the head of Nachvak Fiord is reached. Camera facing left front to line of flight. Grayscale